2012
DOI: 10.1177/1362480612463114
|View full text |Cite
|
Sign up to set email alerts
|

With God on my side: The paradoxical relationship between religious belief and criminality among hardcore street offenders

Abstract: Research has found that many street offenders anticipate an early death, making them less prone to delay gratification, more likely to discount the future costs of crime, and thus more likely to offend. Ironically, many such offenders also hold strong religious convictions, including those related to the punitive afterlife consequences of offending. To reconcile these findings, we interviewed 48 active street offenders to determine their expectation of an early demise, belief in the afterlife, and notions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 86 publications
5
51
0
Order By: Relevance
“…At the same time, however, religiosity does not appear to be effective in inhibiting violent crime. Indeed, as Topalli, Brezina, and Bernhardt (2012) found, religious belief may actually facilitate offending for some people. In their qualitative study of persistent violent offenders, Topalli et al found that the majority of those they interviewed professed strong beliefs in God and, although they did not attend church services, they reported engaging in prayer.…”
Section: Introductionmentioning
confidence: 93%
“…At the same time, however, religiosity does not appear to be effective in inhibiting violent crime. Indeed, as Topalli, Brezina, and Bernhardt (2012) found, religious belief may actually facilitate offending for some people. In their qualitative study of persistent violent offenders, Topalli et al found that the majority of those they interviewed professed strong beliefs in God and, although they did not attend church services, they reported engaging in prayer.…”
Section: Introductionmentioning
confidence: 93%
“…When considering how national context might affect the relationship between religiosity and intimate partner violence, we can draw upon the more general research on how contextual factors condition the effects of religiosity on crime and juvenile delinquency (Desmond and Kraus ; Finke and Adamczyk ; Grasmick, Bursik, and Cochran ; Hadaway, Elifson, and Petersen ; Jang and Johnson ). As with the link between religiosity and intimate partner violence, the relationship between religiosity and crime is complex (Topalli, Brezina, and Bernhardt ). After Hirschi and Stark's () important study found that religious commitment among youth was not related to measures of delinquency, it spawned a number of studies that sought to replicate it.…”
Section: Theoretical and Empirical Backgroundsmentioning
confidence: 99%
“…This could be problematic for an individual as they would not be foreseeing any potential consequences of their actions or anticipating any future risk that could be a result of their actions or behavior. Previous research has found that religion could be used in self-serving ways by individuals who interpreted religious doctrine in a way that allowed them to justify their behavior, exacerbating their offending (Topalli et al 2013).…”
Section: Discussionmentioning
confidence: 99%